Associations between second‐line glucose‐lowering combination therapies with metformin and HbA1c, body weight, quality of life, hypoglycaemic events and glucose‐lowering treatment intensification: The DISCOVER study. Issue 8 (3rd May 2021) - Khunti, Kamlesh; Charbonnel, Bernard; Cooper, Andrew; Gomes, Marília B.; Ji, Linong; Leigh, Paul; Nicolucci, Antonio; Rathmann, Wolfgang; Shestakova, Marina V.; Siddiqui, Afrah; Tang, Fengming; Watada, Hirotaka; et al.
Abstract: Aim: To explore the effects of second‐line combination therapies with metformin on body weight, HbA1c and health‐related quality of life, as well as the risks of hypoglycaemia and further treatment intensification in the DISCOVER study, a 3‐year, prospective, global observational study of patients with type 2 diabetes initiating second‐line glucose‐lowering therapy. Materials and Methods: Adjusted changes from baseline in weight, HbA1c and 36‐item Short Form Health Survey version 2 (SF‐36v2) summary scores at 6, 12, 24 and 36 months were assessed using linear mixed models. Risk of hypoglycaemia and further intensification were assessed using interval censored analyses. Results: At baseline, 7613 patients received metformin in combination with a sulphonylurea (SU; 40.9%), a dipeptidyl peptidase‐4 (DPP‐4) inhibitor (48.3%), a sodium‐glucose co‐transporter‐2 (SGLT‐2) inhibitor (8.3%) or a glucagon‐like peptide‐1 (GLP‐1) receptor agonist (2.4%). After 36 months, all combinations showed similar reductions in HbA1c (0.8%‐1.0%), however, metformin plus a DPP‐4 inhibitor, an SGLT‐2 inhibitor or a GLP‐1 receptor agonist was associated with greater weight loss (1.9, 2.9 and 5.0 kg, respectively) than metformin plus an SU (1.3 kg, P  < .0001). Proportions of further treatment intensification were similar across combinations (19.9%‐26.2%). Patients prescribed metformin plus an SU more often reported one or more hypoglycaemic events (11.9%) than other combinations (3.9%‐6.4%, P  < .0001). SF‐36v2 summary scores were typically lowest among patients prescribed metformin and an SU. Conclusions: Combinations of metformin with an SU were associated with the lowest weight reduction, highest risk of hypoglycaemia and lower SF‐36v2 scores.